Efficient Synthesis of Anastrephin via the Allylic Substitution for Quaternary Carbon Construction - Wada, Kyohei; Sakai, Masahiro; Kawashima, Hidehisa; Ogawa, Narihito; Kobayashi, Yuichi (Synlett, 2016)
Lactone-moiety-attached 2-cyclohexylideneethyl picolinate was prepared through the OH-directed epoxidation (98% ds) of (R)-3-methylcyclohex-2-en-1-ol (99% ee), Horner–Wadsworth–Emmons olefination, conversion to the allylic moiety, and epoxide ring opening with Et2AlCH2CO2t-Bu. The allylic substitution of the picolinate with Me2CuMgBr·MgBr2 furnished a quaternary carbon center with 92% ds. Finally, the lactonization of the product, the tert-butyl ester of the seco acid, under acidic conditions, afforded (–)-anastrephin.
Keywords: anastrephin; quaternary carbon; asymmetric synthesis; allylic substitution; copper reagent; picolinate